The effect of capitalization on the competition-stability Nexus: Evidence from dual banking systems - Indria Ernaningsih (17871056) (2023)
The purpose of this paper is investigate how bank capitalization affects the relationship between competition and bank stability in dual banking systems. Using bank-level and country-level data from 17 countries over the period 2000–2019, the evidence shows a U-shaped relationship between competition and bank stability highlighting the dual importance of the franchise value and the risk-shifting paradigms in dual banking systems. The comparative analysis between conventional banks (CBs, hereafter) and Islamic banks (IBs, hereafter) reveals that, compared to CBs, competition is more detrimental to the stability of IBs. Importantly, our analysis reveals that higher bank capitalization moderates the negative effect of competition on bank stability and that the magnitude of the effect is similar between CBs and IBs. Other Information Published in: Pacific-Basin Finance Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.pacfin.2023.102152